Peran Strategi Pembelajaran dan Implementasinya Pada Era Digital - Indah Khairany; Maghfirah Chairunnisa; Muhammad Arifin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
In the digital age, effective learning strategies not only focus on delivering material, but also involve students actively in the learning process, encourage deep understanding, and develop skills relevant to the digital world. In addition to the role of learning strategies, their implementation is also key in ensuring learning success in this digital era. The objective of this research is to explore the importance of learning strategies and their application in the digital era. To achieve this, a qualitative research approach is employed with data being sourced from a range of relevant literature. The Miles and Huberman model is utilized as the data analysis methodology, encompassing process of data reduction, data presentation, and conclusion drawing. The role of learning strategies in digital era is supporting factors that help increase student learning motivation, achieve learning goals, and update teacher teaching skills. The implementation of learning strategies in the current digital era are 1) Learning models such as blended learning, distance learning, mobile learning and virtual learning environment. 2) Learning innovations such as google sites, whatsapp, teamviewer, remote utilities, aeroadmin, google drive and google forms. 3) Digital learning design developed by applying the principles of independence, flexibility, contemporary, mobility and suitability to the level of need.